Development of a Method for the Synthesis of 4-Aryl-Functionalized 2-Azabicyclo[3.2.1]octanes - Armstrong, Ian S.; Bergmeier, Stephen C. (Synthesis, 2017)
A method for the synthesis of 4-substituted azabicyclo[3.2.1]octanes from N-tosyl-2-azabicyclo[3.2.1]octa-3,6-diene, a versatile bicyclic heterocycle not commonly used in medicinal chemistry research, is presented. The method uses bromination, followed by Suzuki coupling, and subsequent reduction and deprotection. The desired 4-substituted azabicyclo[3.2.1]octanes were obtained in moderate to high yields.
Keywords: Suzuki coupling; heterocycles; palladium; bicyclic compounds; scaffolds